2020
DOI: 10.3389/fped.2020.577673
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Lung Function at Preschool Age in Survivors of Very Low Birth Weight Preterm Infants

Abstract: Background: Survivors of preterm birth are at risk of long-term respiratory consequences. The objective of this prospective study was to assess pulmonary function at preschool age of former very low birth weight (VLBW) preterm children. Methods: Lung function of children born preterm and term controls aged 5–6 years were assessed by spirometry. The results were converted to z-scores. A questionnaire regarding respiratory symptoms was completed. Associations to gestational age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
1
11
1
1
Order By: Relevance
“…Reduced small airway patency, as assessed by FEF 25−75 , has been reported during different stages of infancy (26,(28)(29)(30)(31). In our study, all groups showed a reduction of FEF 25−75 relative to the reference population.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Reduced small airway patency, as assessed by FEF 25−75 , has been reported during different stages of infancy (26,(28)(29)(30)(31). In our study, all groups showed a reduction of FEF 25−75 relative to the reference population.…”
Section: Discussionsupporting
confidence: 67%
“…this technique in preschool age children (26). The results of a previous study (15) that analyzed the suitability of this technique for assessment of lung function in healthy preschoolers support widespread application of the GLI-2012 reference equations.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Kitchen et al ( 24 ) found that lung function was similar in very low birth weight children compared to normal weight birth ones at 8 years of age, despite very low birth weight children suffered more frequently from wheezing in the first 2 years of life. In a recent study performed in preschool aged children, a similar lung function in mild BPD ex-preterm subjects compared to ex-preterm ones without BPD and term controls has been shown, suggesting that mild BPD might not lead to long-term respiratory consequences ( 21 ). The available conflicting findings might be partially explained by the small study sample size, the heterogeneity in the definition of BPD and in the lung function methods utilized, and the different age in which lung function was assessed in cross-sectional studies.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific evidence is still conflicting regarding the persistence of impaired lung function in expreterm children. On one hand, a lot of studies showed lung function impairment in preterm children (19)(20)(21). On the other hand, several studies observed inconsistent association between birth weight and FEV1/FVC (22,23).…”
Section: Discussionmentioning
confidence: 99%